W sprawie wytwórczości szklarskiej w celtyckim oppidum w Starym Hradisku na Morawach - Olczak, Jerzy (Folia Praehistorica Posnaniensia, 2018)
Discussion presented in the article is based upon analysis of glass fragments from the late La Tene oppidum. Existence of the jewellery manufacture workshop in Stare Hradisko, producing bracelets and possibly also beads of dark-blue, dark-yellow and green glass of external origin, is speculated based upon chemical composition of 5 fragments as well as morphological analysis. Further complex studies are postulated, which will facilitate unequivocal testing of the speculation about existence of glass works in StareHradisko. Analysed samples revealed presence of the soda-calcium-aluminium-silicon as well as the soda-calcium-lead-aluminium-silicon glass.